Gaz Alafi: A Traditional Dessert in the Middle East With Anticancer, Immunomodulatory, and Antimicrobial Activities - Al Safi, Meena A.; Rashid, Hasan M.; Afifi, Fatma U.; Talib, Wamidh H. (Frontiers in Nutrition, 2022)
Background: From the earliest times, manna has been widely used as a tasty local sweet or folk medicine. The type of manna being investigated in the present study is called Gaz-alafi, a mixture of insect and Quercus brantii leaves secretions from oak forests in the north of Iraq and west of Iran. Methods: Water and ethanol extracts were made. The phytochemical examination included total phenolic contents using the Folin-Ciocalteu method and LC-MS to analyze the composition. Gallic acid and catechin were detected in both extracts, and tiliroside added more value to the ethanol extract phenolic content. Cytotoxic activities of Gaz alafi were evaluated against breast cancer cell lines and compared to normal cell lines and doxorubicin using the MTT assay method. Antimicrobial properties were assessed against E. coli, P. aeruginosa, S. aureus, B. subtilis, and C. albicans using the dilution method of the micro-titer plate. Serum levels of interferon-gamma, interleukin IL-2, IL-4, and IL-10 of tumor implanted, and normal mice were measured using ELISA. The effect on splenocyte proliferation was evaluated using the MTT assay. Macrophage function was assessed using nitro blue tetrazolium assay, whereas pinocytosis was evaluated using the neutral red method. Ten days after inoculation, changes in tumor size, survival rates, levels of AST, ALT, and creatinine were quantified. Results: The growth of cancer cells was inhibited by Gaz alafi ethanol extract. An alteration in IFN- γ, IL-2, IL-4 levels towards antiproliferation immune response were noted for both extracts. The aqueous extract efficiently stimulated lymphocyte proliferation, phagocytosis, and pinocytosis, followed by the ethanol extracts with moderate activity. After treating the mice with ethanol extracts, a significant reduction in tumor size and several undetected tumors was recorded. Conclusions: Studied extracts exhibited promising anticancer and immunostimulatory effects strongly related to the active components of Gaz alafi.